The falls. Covenant of Grace [videorecording (DVD)] - Farmer, Benjamin; Ferrucci, Nick; Jackson, Curtis Edward (Breaking Glass Pictures, 2016)
Chris and RJ, former Mormon missionaries who fell in love seven years ago, are struggling to make their relationship work amid conflicts with their families and their faith. Determined to finally find closure and put the past behind them, the two men set in motion a quest for unconditional love that ultimately leads to the very top of LDS leadership. The sensitive portrayal of this storyline is what has made this trilogy resonate with audiences around the world.